Community-acquired urinary tract infections: causative agents and their resistance to antimicrobial drugs - Djordjević, Zorana; Folić, Marko; Janković, Slobodan (Vojnosanitetski pregled, 2017)
Background/Aim. Urinary tract infections (UTIs) are among the most common infections in outpatients. The aim of this study was to define the causative agents of urinary tract infections and their resistance to antimicrobial drugs in the urban area of central Serbia, as well as to evaluate eventual differences associated with age and gender of the patients. Methods. This retrospective study analysed data taken from routine, consecutively collected urine cultures of outpatients with symptomatic UTIs, collected from the Department of Microbiology, Institute of Public Health in Kragujevac, Serbia, from January 2009 to December 2013. Results. There were 71,905 urine cultures, and 24,713 (34.37%) of them were positive for bacterial pathogens. The most common pathogen was Escherichia coli (E. coli) (56.56%), followed by Klebsiella spp. (16.20%), Proteus spp. (14.68%), Enterococcus spp. (5.29%) and Pseudomonas aeruginosa (3.74%). E. coli and Enterococcus spp. isolation rates were lower in males ≥ 60 years old (23.71% and 4.87%, respectively), while Klebsiella spp. was more prevalent in this group (32.06%). The most common causative agents isolated from 15–29 years old male patients were Enterococcus spp. and Pseudomonas aeruginosa (13.28% each). Among women, the isolation rate of E.coli was high in all age groups (around 70%). Proteus spp. was frequently isolated from females ≤ 14 years old (13.27%), while Klebsiella spp. was the most frequent in the oldest age female group (10.99%). Conclusion. Choice of antibiotics for treatment of UTIs should be governed not only by the local resistance patterns, but also by gender and age of patients.
Keywords: urinary tract infections; urine; bacteria; drug resistance; microbial; outpatients; serbia; age factors; sex factors